Investigating the Implementation of Online Learning in Remote Learning Context - Nyudak, Dwi Tahamata; Putra, I Nyoman Adi Jaya; Santosa, Made Hery (Journal of Education Research and Evaluation, 2021)
This research aimed at (1) identifying teacher’s cognition towards online learning; (2) identifying the implementation of online learning; (3) identifying the consistency of teacher’s cognition and implementation of online learning; (4) identifying teacher’s perception toward online; (5) identifying students’ perception toward online learning; and (6) identifying parents’ perception toward online learning. In collecting the data, questionnaires, interview and observation checklist analysis were done. The result showed that (1) the teacher had high cognition towards online learning; (2) the teacher did several preparations and there were some procedures applied in online learning in remote learning context; (3) teacher’s cognition and the implementation were consistent; (4) The teacher perceived online learning positively; (5) the students perceived online learning positively with some surprising information from the open-ended questionnaire which was in different side from the closed ended questionnaire; (6) the parents perceived online learning in a balance view at first but the open-ended questionnaire stood on negative side.